Efektivitas Penegakan Hukum Pidana Dalam Penanganan Pelanggaran Lalu Lintas - Lendrie Adi P. Rembet (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
A large number of road users who often pass by on the highway every day can cause problems in traffic, one of which is a traffic accident. The purpose of this study was to determine the effectiveness of criminal law enforcement in handling traffic violations. The research method used is qualitative research through literature study by applying the legal and statutory approaches that apply in Indonesia. The goal of public protection and safety can be achieved through enforcing criminal law in traffic violations. By imposing strict criminal sanctions, it is expected to prevent repeated violations and provide a deterrent effect to offenders. Justice and responsibility are important principles in enforcing criminal law on traffic violations.